Complex fraction comparisons and the natural number bias: The role of benchmarks. (June 2020) - Obersteiner, Andreas; Alibali, Martha Wagner; Marupudi, Vijay
Abstract: People are often better at comparing fractions when the larger fraction has the larger rather than the smaller natural number components. However, there is conflicting evidence about whether this "natural number bias" occurs for complex fraction comparisons (e.g., 23/52 vs. 11/19). It is also unclear whether using benchmarks such as 1/2 or 1/4 enhances performance and reduces the bias (e.g., 11/19 > 1/2 and 23/52 < 1/2, hence 11/19 > 23/52). We asked 107 adults to solve complex fraction comparisons that did or did not afford using benchmarks, and we assessed response time and accuracy. We found a reverse bias (i.e., smaller components—larger fraction) that was greater among participants with lower mathematics experience. Fractions' proximity to 0 or 1 facilitated performance and decreased bias; effects of other benchmarks were nonsignificant. These results challenge the generality of the natural number bias in fraction comparison and highlight its variability. Highlights: Adults show a "smaller components—larger fraction" bias in complex fraction comparison. The strength of the bias depends on problem type and mathematics experience. Proximity to salient benchmarks—specifically 0 and 1—can help people overcome the bias. Large inter-individual variability challenges the notion of a general bias.